How Are We All Doing (Revisited)?: A Message From the Editor-in-Chief (Journal on Excellence in College Teaching, 2024)
The articles in this issue of the Journal respond to the need to check in with both faculty and students to support their well-being and performance as individuals, teachers, and learners.